An investigation into network handover procedure in mobile broadband system - Thanee Eub-arb; Ahmed, Erke, Tapio; Kazi Mohiuddin; Lehtimaki, Seppo J.; Royal Thai Government (Bangkok : Asian Institute of Technology, 1997)
The main objective of the Mobile Broadband System (MBS) is to provide a mobile system to support broadband services. As in the cellular mobile network, the procedure for supporting handover of mobile terminal in the MBS system, called network handover scheme, is one of the most important aspects in ongoing research for this system. The Virtual Connection Tree (VCT) -based network handover scheme is assigned to be one possible proposed network handover scheme in the MBS system. The major problem of this scheme is that it cannot preserve cell sequence and it makes additional cell loss during handover. Those unsequenced cells and lost cells cause high cell loss ratio in the network. In current published papers the performance parameters of the VCT-based network handover scheme have, up to now, been investigated only for fixed bandwidth source model and only for connection level traffic despite the fact this scheme is designed to support diverse kinds of traffic source. This thesis investigates the performance of VCT-based network handover scheme in both connection level and cell level traffic for various kinds of traffic. The main objective of this thesis is to improve the cell loss performance of VCT-based network handover scheme. A mechanism is proposed to minimize the cell loss caused by the handover procedure. In the proposed scheme, buffers for each call are provided to improve cell loss performance. The simulation results show that cell loss performance can be considerably improved for all kinds of traffic by proposed network handover scheme. This enhancement of cell loss performance results in extra cell delay due to the buffer. However, in most cases the cell delays in the proposed buffer for all traffic sources are at an acceptable level according to their Quality of Service (QoS) requirements. This thesis also shows the characteristics of cell delay distributions investigated in different conditions.
Thesis (M.Eng.) - Asian Institute of Technology, 1997
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering.
Keywords: Mobile communication systems